The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2003
DOI: 10.1207/s15327604jaws0601_01
|View full text |Cite
|
Sign up to set email alerts
|

Dog Keeping in Taiwan: Its Contribution to the Problem of Free-Roaming Dogs

Abstract: This study conducted a quantitative ethnographic analysis of the influence of demographic factors and early experience (childhood exposure to dogs) on Taiwanese dog-keeping practices and behavior. A telephone survey of a randomly selected sample of 2001 Taiwan residents determined their dog ownership histories, current patterns of dog ownership and disposal, and other dog-related activities. The results suggest that low rates of neutering, easy availability of low- or no-cost puppies, a tendency to allow owned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
66
3
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 19 publications
6
66
3
3
Order By: Relevance
“…A case of a Labrador owner who abandoned his dog on a beach so that "someone would claim it" is likely atypical only as far as the abandoned dog was not a potcake. Elsewhere, such as in Taiwan (Hsu, Severinghaus, & Serpell, 2003), it has been shown that dog-keeping practices contribute to the roaming dog population, and the linkage is most likely to be prevalent in The Bahamas.…”
Section: Excess Dogsmentioning
confidence: 99%
“…A case of a Labrador owner who abandoned his dog on a beach so that "someone would claim it" is likely atypical only as far as the abandoned dog was not a potcake. Elsewhere, such as in Taiwan (Hsu, Severinghaus, & Serpell, 2003), it has been shown that dog-keeping practices contribute to the roaming dog population, and the linkage is most likely to be prevalent in The Bahamas.…”
Section: Excess Dogsmentioning
confidence: 99%
“…In Europe, the largest pet dog populations are in France, amounting to 8.8 million, while both Italy and Poland each have over 7.5 million. Currently, the global dog population (pet, roaming, stray, and feral animals) is estimated to be more than 500 million [1].…”
Section: Introductionmentioning
confidence: 99%
“…The lack of confinement is not unique to the Caribbean; rather, it appears to be common in less-developed countries (Hsu, Severinghaus, & Serpell, 2003). However, the fact that some owners adopted dogs from the street suggests that there are uncared-for dogs who may have been passively, if not actively, abandoned.…”
mentioning
confidence: 99%